Making a difference for children born with a cleft in the UK. (June 2019) - Sandy, Jonathan R
This short review is an opportunity to focus on significant positive changes for those children born with some form of oro-facial clefting and who are treated in a centralised service within the National Health Service (NHS). There has also been an opportunity to provide a focus for research as part of this service model. Orthodontists have played a key role in all aspects of this and will continue to be central to further improvements in caring for cleft children.